Characterisation of genes essential for pathogenesis of fish adapted S. agalactiae - Santi, Morena (2022)
Streptococcus agalactiae, or Group B Streptococcus (GBS), is a highly infectious zoonotic pathogen, responsible for streptococcosis in fish, meningitis and septicaemia in humans and mastitis in cattle. In fish, it manifests as septicaemia, resulting in high morbidity and mortality in a number of wild and farmed species, especially tilapia. In the current study the genome of the fish isolate Streptococcus agalactiae 01173 was sequenced and shown to be representative of those isolated from fish. A population of randomly mutagenized strains were generated in S. agalactiae 01173 using the pGh9:ISS1 insertional mutagenesis system. Populations of mutants in which between 1759 and 1946 of the 1969 protein coding sequences were mutated and analysed using the transposon insertion sequencing technique, Pragmatic Insertional Mutation Mapping System, to identify genes required for survival in relevant biological conditions. This approach led to the identification of genes that might contribute to the survival of S. agalactiae during infection in its natural host. Following growth in tilapia serum, 66 such genes were identified. A further 52 genes were identified as conditionally essential in the presence of hydrogen peroxide and 98 genes were found to be conditionally essential in the presence of the antimicrobial peptide, TP4. Three genes, dltX, atpB and atpC were found to be essential in all the three phenotypes. This represents the first transposon insertion sequencing study on a fish adapted S. agalactiae, and highlights its potential use to rapidly identify potential targets for further investigation and exploitation in the generation of vaccines and new therapeutics.